2018
DOI: 10.2106/jbjs.17.00376
|View full text |Cite
|
Sign up to set email alerts
|

Femoral Version Abnormalities Significantly Outweigh Effect of Cam Impingement on Hip Internal Rotation

Abstract: It is common clinical practice to ascribe loss of hip internal rotation to the presence of a cam lesion and to assume that arthroscopic femoral osteoplasty will substantially improve internal rotation postoperatively. Our study shows that the cam lesion is more intimately tied to hip flexion than to hip internal rotation. This result directly impacts the clinical assessment of a patient presenting with radiographic findings of FAI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(59 citation statements)
references
References 33 publications
3
53
0
Order By: Relevance
“…Few publications define the amount of safe bone resection on the femoral side before creating an increased risk of stress fracture, and there is no consensus about the depth and extension of resection. Kraeutler et al 9 clarified the importance of the femoral torsional profile in FAI pathomorphology. According to their study, cam deformity limits flexion while retrotorsion of the neck limits internal rotation.…”
Section: Fai Treatment: An Update Indications and Type Of Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…Few publications define the amount of safe bone resection on the femoral side before creating an increased risk of stress fracture, and there is no consensus about the depth and extension of resection. Kraeutler et al 9 clarified the importance of the femoral torsional profile in FAI pathomorphology. According to their study, cam deformity limits flexion while retrotorsion of the neck limits internal rotation.…”
Section: Fai Treatment: An Update Indications and Type Of Surgerymentioning
confidence: 99%
“…predominant mechanism depends on the direction of movement. 9 In the late 1990s, the surgical dislocation technique developed by Ganz direct inspection of these mechanisms of cartilage and labral damage and was considered the keystone for understanding one of the most common mechanical risk factors of early hip osteoarthritis. 3,10,11 Open or arthroscopic trimming of the acetabular margin with labral refixation and head-neck waist restoration has been established as the standard treatment of FAI syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Thus assessment of torsion in young patients with hip pain is mandatory. 119 Interestingly, patients with pincer-type FAIS have a larger femoral antetorsion than patients with cam-type FAIS, 115 although this parameter per se does not differ significantly between symptomatic and healthy individuals. 53,115 Recently, the supra-and infra-trochanteric components of femoral torsion were demonstrated to differ substantially between hip disorders because patients with DDH have predominantly increased infra-trochanteric torsion, whereas patients with pincer-type FAIS have increased supra-trochanteric torsion.…”
Section: Femoral Torsionmentioning
confidence: 99%
“…63,64 Until recently the assessment of FAI mainly focused on proximal femoral head morphology, acetabular coverage and version. However, it was shown that femoral torsion considerably affects the impingement-free range of motion 65,66 and that severely abnormal femoral torsion may be present in one of six hips undergoing an MRI of the hip. 67 This is important because decreased femoral torsion yields worse outcomes after arthroscopic FAI correction and may require additional rotational femoral osteotomies in severe cases.…”
Section: Impingement Morphologiesmentioning
confidence: 99%